2008
DOI: 10.1097/jto.0b013e31817c6b68
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial Comparing Single-Agent Paclitaxel Poliglumex (CT-2103, PPX) with Single-Agent Gemcitabine or Vinorelbine for the Treatment of PS 2 Patients with Chemotherapy-Naïve Advanced Non-small Cell Lung Cancer

Abstract: Single-agent PPX, dosed at 175 mg/m, is active and well tolerated in PS 2 patients with advanced NSCLC. Patients on PPX required fewer red blood cell transfusions, hematopoietic growth factors, opioid analgesics, and clinic visits than patients receiving gemcitabine or vinorelbine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(53 citation statements)
references
References 16 publications
(8 reference statements)
0
53
0
Order By: Relevance
“…10 The poly(L-glutamic acid)-paclitaxel conjugate (CT-2103) is considered the most advanced polymerpaclitaxel conjugate to date. 4 CT-2103 has been investigated in Phase III trials, but has not been approved as yet by the Food and Drug Administration, [11][12][13] so there is still a need for an efficacious polymer-paclitaxel conjugate for the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10 The poly(L-glutamic acid)-paclitaxel conjugate (CT-2103) is considered the most advanced polymerpaclitaxel conjugate to date. 4 CT-2103 has been investigated in Phase III trials, but has not been approved as yet by the Food and Drug Administration, [11][12][13] so there is still a need for an efficacious polymer-paclitaxel conjugate for the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I evaluations of OPAXIO™ in patients with advanced solid malignancies have revealed MTDs of 233 mg/m 2 (dosed once every 3 weeks) (62), 177 mg/m 2 (dosed once every 2 weeks) (62), and 70 mg/m 2 (dose once weekly) (65), all of which are enhancements over observed MTDs for Taxol® given at the same schedule. While there are indications of antitumor activity in preclinical models and some early clinical studies, more recent singleagent Phase III studies have failed to show an OPAXIO™-induced significance enhancement in the duration of overall survival for patients with non-smallcell lung cancer (66)(67)(68).…”
Section: Nanoparticle/nanoscaled Formulations Of Small Moleculesmentioning
confidence: 97%
“…Despite very promising data in preclinical and early phase clinical studies, data from several phase III clinical studies showed that PPX is not signifi cantly more effective than standard treatments [ 54 ]. For example, the conjugate did not show any survival benefi t, compared to either gemcitabine or vinorelbine single agent chemotherapeutic, in a randomized phase III trial in patients with advanced non-small cell lung cancer (NSCLC) [ 55 ]. Similarly, no survival benefi t was found when PPX was used as a second line of treatment against NSCLC in a phase III trial on 849 patients, as compared to docetaxel [ 56 ].…”
Section: Drug-polymer Conjugatesmentioning
confidence: 98%